2011
DOI: 10.3389/fphys.2011.00064
|View full text |Cite
|
Sign up to set email alerts
|

Face piercing (body art): choosing pleasure vs. possible pain and posture instability

Abstract: Piercings (body art, i.e., with jewelry) are more and more widespread. They can induce various complications such as infections, allergies, headaches, and various skin, cartilage, or dental problems, and represent a public health problem. We draw attention to possible side effects resulting from face piercing complications observed on four young adults such as eye misalignment, decreased postural control efficiency, and non-specific chronic back pain with associated comorbidity. We found that the origin was pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Because many of these individuals do not seek psychiatric treatment, the dermatologist may need to assume this role to understand the behavioral motivations of these patients through evaluation of their piercings in order to help them mentally [38]. Because of the often sensitive nature of piercings, physicians must assume a non-judgmental approach that encourages patients to seek treatment from medical professionals rather than their piercer or the internet [5,27,33,34,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because many of these individuals do not seek psychiatric treatment, the dermatologist may need to assume this role to understand the behavioral motivations of these patients through evaluation of their piercings in order to help them mentally [38]. Because of the often sensitive nature of piercings, physicians must assume a non-judgmental approach that encourages patients to seek treatment from medical professionals rather than their piercer or the internet [5,27,33,34,39].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is an increase in the prevalence and social acceptance of intimate body piercings, there is a dearth of literature on the associated health risks and complications related to its practice [3]. All piercings share a number of complications such as infection, trauma, hypersensitivity reactions, bleeding, keloid formation, and scarring [5,6]. When infections occur, Staphylococcus aureus, Group A Streptococci, and Pseudomonas species are the most commonly cultured organisms [7].…”
Section: Dermatology Online Journal || Reviewmentioning
confidence: 99%
“…In non-specific chronic pain, VH is present and is <1 diopter ( 17 , 18 ). It was reported that in patients with non-specific chronic pain associated with VH, a specific proprioceptive physiotherapy acting on oropharynx, temporomandibular joint, and/or pelvis most of the time restored VO immediately ( 14 ), diminished pain [evaluated with a subjective visual analog scale (VAS) ( 19 , 20 )], normalized behavior in the balance tests, improved mobility of peripheral joints and of the spine including the neck after initial alternation, but this remains to be precisely measured ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%